Engineered Skin Tissue Equivalents for Product Evaluation and Therapeutic Applications. Issue 7 (17th May 2019) - Suhail, Sana; Sardashti, Naseem; Jaiswal, Devina; Rudraiah, Swetha; Misra, Manoj; Kumbar, Sangamesh G.
Abstract : The current status of skin tissue equivalents that have emerged as relevant tools in commercial and therapeutic product development applications is reviewed. Due to the rise of animal welfare concerns, numerous companies have designed skin model alternatives to assess the efficacy of pharmaceutical, skincare, and cosmetic products in an in vitro setting, decreasing the dependency on such methods. Skin models have also made an impact in determining the root causes of skin diseases. When designing a skin model, there are various chemical and physical considerations that need to be considered to produce a biomimetic design. This includes designing a structure that mimics the structural characteristics and mechanical strength needed for tribological property measurement and toxicological testing. Recently, various commercial products have made significant progress towards achieving a native skin alternative. Further research involve the development of a functional bilayered model that mimics the constituent properties of the native epidermis and dermis. In this article, the skin models are divided into three categories: in vitro epidermal skin equivalents, in vitro full‐thickness skin equivalents, and clinical skin equivalents. A description of skin model characteristics, testing methods, applications, and potential improvements is presented. Abstract : The skin tissue equivalents that have emerged as relevant tools in commercial and therapeutic product development applications is reviewed. A description of skin model characteristics, applications, and potential improvements is presented. With continuous research, a fully functional model replicating the properties of the epidermis, dermis, and hypodermis can be expected in the coming years.